UPAYA JAPAN INTERNATIONAL COOPERATION AGENCY DALAM IMPLEMENTASI OFFICIAL DEVELOPMENT ASSISTANCE UNTUK MEMBANGUN SEKTOR PERTANIAN TIMOR-LESTE - Costa Tavares, Agostinho Da; Wiranata, I Made Anom; Kawitri Resem, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
A BS TRAK Timor-Leste as a relatively young country needs foreign aid to develop it’s agricultural sector especially sustainable agriculture. Japan International Cooperation Agency (JICA) is Japanese Government development agency that distributes Official Development Asistance (ODA) bilaterally to Government of Timor-Leste. One of the assistance that provided by JICA to the Timor-Leste is Study Community-Based Integrated Watershed Management in Laclo and and Comoro River Basins which classified as technical cooperation. This assistance is provided in order to assist the sustainable agriculture in Timor-Leste . The aim of this research to describe the Efforts of JICA in the implementation of ODA to build the agricultural sector in Timor-Leste as a proponent of the peacebuilding process in Timor-Leste through the Study Community-Based Integrated Watershed Management in Laclo and and Comoro River Basins in the year 2005-2010. Development agency, foreign aid, agriculture, and sustainable agriculture are concepts that used in this research. Keywords : Sustainable agriculture, development agency, foreign aid, Timor-Leste